1975
DOI: 10.1002/1097-0142(197501)35:1<5::aid-cncr2820350103>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for inhibiting tumor metastases

Abstract: Of the four major biological mechanisms of cancer spread, hematogenous dissemination is perhaps the most significant, as it usually heralds a fatal outcome for the patient. Recent experimental approaches have shown ways of altering the metastatic process and even totally inhibiting it in some animal models. It appears that these models may be applicable to certain human cancers. To prevent hematogenous metastasis formation the process must be inhibited at any one of four levels: 1) growth of the primary; 2) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Some investigators have sought to explore the ~fibrin hypothesis" but did so in ways that were not likely to yield conclusive results. Blockbuster attempts to thwart clotting as by systemic heparin or warfarin treatment or to inhibit fibrinolysis, as with selected protease inhibitors, led to confusing and often contradictory results in both cancer patients and in animal tumor models (12,25,(164)(165)(166)(167)(168)(169)(170)(171), although a recent study (169), now pending independent confirmation, has reported sucessful treatment of lung cancer patients with warfarin as a supplement to conventional therapy. Interpretation of these experiments has been made even more difficult because the investigators, without exception, failed to monitor the effects of their therapy on local tumor-associated fibrin, measuring only the effects on plasma clottability or fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have sought to explore the ~fibrin hypothesis" but did so in ways that were not likely to yield conclusive results. Blockbuster attempts to thwart clotting as by systemic heparin or warfarin treatment or to inhibit fibrinolysis, as with selected protease inhibitors, led to confusing and often contradictory results in both cancer patients and in animal tumor models (12,25,(164)(165)(166)(167)(168)(169)(170)(171), although a recent study (169), now pending independent confirmation, has reported sucessful treatment of lung cancer patients with warfarin as a supplement to conventional therapy. Interpretation of these experiments has been made even more difficult because the investigators, without exception, failed to monitor the effects of their therapy on local tumor-associated fibrin, measuring only the effects on plasma clottability or fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Withers and Milas (1973) found that the lung-cloning efficiency of a chemically induced C3H mouse fibrosarcoma was increased by a factor of 10 after 1000 rad thoracic irradiation, this maximum value occurring 1 day after irradiation. Bearing in mind that van Putten et al (1975) (Malmgren, 1968;Hoover and Ketcham, 1975 Brown (1973) found that radiationinduced enhancement of lung cloning was associated with a reduced clearance rate of 1251-labelled cells from the lungs during the first 2 days after implantation. Essentially all the labelled cells were trapped in the lungs within 5 min, but within 12 h the irradiated lungs retained significantly more radioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the current literature where the bulk of research studies on the pharmacology of metastases have focused almost exclusively on the mechanisms by which metastatic tumor cells spread rather than on the proliferative capacity of the same cells established in distant organs. In analyzing the metastatic cascade in animal tumor models several discrete stages in the metastatic process have been studied in detail (2,4,10,11) and several have been proposed as sites for therapeutic intervention (12)(13)(14). Many of these studies have been instrumental in examining the biology, pharmacology and biochemistry of tumor cell metastasis but the prospects of exploiting this information in the design of mechanism-based drugs which display improved activity against established metastases, are for reasons described above, remote, Compounds with proposed 'antimetastatic' activity like inhibitors of tumor cell invasion (protease inhibitors and disruptors of microtubule function) (15)(16)(17)(18)(19)(20)(21), antagonists of tumor cell-platelet interactions (prostacyclin thromboxane antagonists, calcium channel blockers) (22)(23) and blockers of tumor cell arrest (laminin fragments) (33, 34) may serve as useful tool compounds to yield insight into the pathogenesis of metastasis and may even find limited clinical utility in the prophylactic discouragement of tumor cell spread.…”
Section: Therapeutic Targetmentioning
confidence: 99%